Estimation of LC50 and its Confidence Interval for the Effect of Nano-Zero Valent Iron on the Freshwater Zooplankton Species Daphnia magna - Mohd Jaafar, Izazy Nur; Ahmad, Siti Aqlima; Yasid, Nur Adeela (Journal of Environmental Microbiology and Toxicology, 2018)
Determination of lethal concentration (LC50) of toxicants leading to 50% mortality of test samples in a toxicity test is very important and could be achieved by running Probit analysis. The response is binomial (death or no death) and relationship between response and various doses or concentrations is typically sigmoid. The Probit value can either be manually calculated by hand, or automatically calculated by computer software using a higher accuracy estimation method, namely the maximum likelihood principle. When a published toxicity study failed to report the 95% confidence interval values, the results can be recalculated via software. In this study, the LC50 and 95% confidence interval values of the effect of nano-zero valent iron towards the freshwater zooplankton Daphnia magna is recalculated by employing the Probit analysis in the SPSS software. The results of the Probit modelling exercise gave an LC50 value of 0.405 mg/L (95% confidence interval, CI was from 0.047 to 0.953) for Nanofer 25S, 0.706 mg/L (95% CI was from 0.151 to 3.203) for Nanofer STAR, 1.020 mg/L (95% CI was from 0.683 to 1.445) for Fe2+ and 5.834 mg/L (95% CI was from 4.190 to 9.189) for Fe3+. The wide 95% confidence interval curves for Nanofer 25S and Nanofer STAR indicate a large uncertainty meaning more data in the future should be obtained to increase the CI. The sub lethal concentration (SLC), which is one fourth of the LC50 value for Nanofer 25S, Nanofer STAR, Fe2+ and Fe3+ were 0.101, 0.176, 0.255 and 1.458 mg/L, respectively.